Jordan : Second Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Augmentation of Access, and Modification of Performance Criteria-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2021)
Early success in containing the spread of COVID-19 has been challenged by two subsequent waves of the pandemic. Timely and effective fiscal and monetary policy responses helped contain the contraction in activity to 1.6 percent in 2020, shallower than the 3 percent expected at the first review. The authorities have also made significant efforts to protect jobs and the most vulnerable. Still, unemployment has surged to a record 25 percent in Q4 2020, with youth unemployment at 55 percent. The impact on fiscal and external balances has been significant, with public debt reaching 88 percent of GDP at end-2020. Nonetheless, despite the challenges from new virus variants and weaker tourism prospects, macroeconomic stability has been maintained, thanks to the authorities' proactive policy stance; and a moderate 2 percent growth rate is projected for 2021 (slightly below the 2.5 percent projected in the first review), with a near-full reopening expected in the summer. The new parliament extended a vote of confidence to the incoming government in January, and approved the 2021 budget-consistent with the program-in February.